PENGARUH MODERENISASI TERHADAP RUMAH TINGGAL TRADISIONAL DI DESA ADAT PENGLIPURAN KABUPATEN BANGLI - Primadi, I Gede; Adhimastra, I Nyoman (Jurnal Anala, 2017)
Penglipuran Traditional Village is one of the tourist village in Bali is located in Kubu Village, District Bangli, Bangli regency. As one of the attractions of rural, Penglipuran has a tourist attraction in the form of a spatial pattern and unique traditional architecture, traditions and social and cultural life of society is typical, and the presence of lush bamboo forest. But lately there is concern on the continued development of tourism in the village's existence home building traditional population is already threatened with the development of modernization and increasing the level of the economy of local communities, and a shift in cultural values of traditional society towards a modern society, as well as the existence of bamboo plants in around the yard of vulnerable populations will be putting land into residential land. It takes a joint effort of government and the community to keep keberadaannnya in the future so that the realization of sustainable development of tourism. This study aims to determine the effect of modernization against the traditional residential houses in the village Penglipuran, and what are the factors that influence. The few things that were influenced modereniasi is in terms of function, material and shape of the building, and ornaments.Keywords: modernization, Village Traditional House Penglipuran